Alcohol-Induced Neuroadaptation Is Orchestrated by the Histone Acetyltransferase CBP - Ghezzi, Alfredo; Li, Xiaolei; Lew, Linda K.; Wijesekera, Thilini P.; Atkinson, Nigel S. (Frontiers in Molecular Neuroscience, 2017)
Homeostatic neural adaptations to alcohol underlie the production of alcohol tolerance and the associated symptoms of withdrawal. These adaptations have been shown to persist for relatively long periods of time and are believed to be of central importance in promoting the addictive state. In Drosophila, a single exposure to alcohol results in long-lasting alcohol tolerance and symptoms of withdrawal following alcohol clearance. These persistent adaptations involve mechanisms such as long-lasting changes in gene expression and perhaps epigenetic restructuring of chromosomal regions. Histone modifications have emerged as important modulators of gene expression and are thought to orchestrate and maintain the expression of multi-gene networks. Previously genes that contribute to tolerance were identified as those that show alcohol-induced changes in histone H4 acetylation following a single alcohol exposure. However, the molecular mediator of the acetylation process that orchestrates their expression remains unknown. Here we show that the Drosophila ortholog of mammalian CBP, nejire, is the histone acetyltransferase involved in regulatory changes producing tolerance — alcohol induces nejire expression, nejire mutations suppress tolerance, and transgenic nejire induction mimics tolerance in alcohol-naive animals. Moreover, we observed that a loss-of-function mutation in the alcohol tolerance gene slo epistatically suppresses the effects of CBP induction on alcohol resistance, linking nejire to a well-established alcohol tolerance gene network. We propose that CBP is a central regulator of the network of genes underlying an alcohol adaptation.